Нереверсивні дволанкові перетворювачі постійної напруги з розділеною комутацією - Івахно, Володимир Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Дисертація присвячена вирішенню актуальної науково-прикладної задачі, яка полягає у розвитку методу та принципів побудови дволанкових обернених нереверсивних перетворювачів постійної напруги з трансформаторною гальванічною розв'язкою. В роботі здійснюється дослідження та розвиток концепції побудови таких перетворювачів на базі відносно нової та мало дослідженої концепції – концепції розділеної комутації. Перетворювачі з розділеною комутацією (ПРК) будуються на базі неоднорідних інверторно-випрямних ланок: одна з ланок побудована на базі топології інвертора напруги (ІН), а інша – інвертора струму (ІС); ланки з'єднуються за допомогою узгоджуючого трансформатора. Спеціальний алгоритм синхронного керування ключами обох ланок – алгоритм розділеної комутації (АРК) – забезпечує сприятливі умови комутації ключів обох ланок: для ключів ланки ІН здійснюється природне (в нулях напруги, zero voltage switching, ZVS) вмикання та примусове снаберне ємнісне вимикання, для ключів ланки ІС – природне (в нулях струму, zero current switching, ZCS) вимикання та примусове снаберне індуктивне вмикання. Нереверсивність перетворювача з ланкою ІС при збереженні властивості оборотності забезпечується присутністю у комутаторі ланки ІС 4-квадрантного ключа (ключів). Дано обґрунтування переваги використання у ланці з більшою величиною постійної напруги ІС з ZCS вимиканням ключів і ІН з ZVS вмиканням ключів для іншої ланки; введено поняття "критичної" частоти перетворення у ПРК з IGBT – такої частоти, вище якої сумарні статичні втрати та втрати вимикання IGBT у ланці ІН будуть вищими за сумарні статичні втрати у IGBT та послідовному діоді ключа ІС при тій ж величинах струму та напруги, що комутуються. При частоті, вищої за "критичну", використання у ПРК більш високовольтової ланки за топологією ІС дає переваги у ККД. Представлені дані для величин "критичних" частот для IGBT провідних виробників різних класів напруг та технологій, згідно яких для класів напруг приладів вище 1700-2500 В, використання високовольтової ланки за топологією ІС є привабливим. Представлено декілька модифікацій схем ПРК. Для ПРК з IGBT у ланці ІС проаналізовано використання, наряду з мостовою схемою з 4-хквадрантними ключами, ряду схем з 4-хквадрантними ключами, але з меншою кількістю IGBT; порівняльний аналіз за критеріями величини сумарної напруги на ввімкнених ключах ланки та вартості показав перевагу схеми з послідовним до обмотки трансформатора 4-квадрантним ключем та з комутатором на IGBT з зворотними діодами за мостовою схемою (6 IGBT замість 8). Для такого ПРК для режиму зворотної передачі енергії (від ланки ІС до ІН) виявлена наявність резонансного інтервалу перезаряду снаберних конденсаторів. Пропонується та досліджується ПРК з асиметричною топологією ланки ІС, в якому струм вторинної обмотки протікає не через 4, а через 3 ввімкнених ключа, що є перевагою. Для режиму передачі енергії від ланки ІН до ланки ІС виявлений новий вид комутації: при вмиканні транзистора 4-хквадрантного ключа, для нього має місце примусове ввімкнення при нульовій напрузі і, не зважаючи на примусовість ввімкнення та стрибкоподібне зростання струму ключа, комутаційні втрати вмикання відсутні. Запропоновано обмеження величини індуктивності розсіяння як снабера вмикання на рівні, який забезпечує відносну сумарну тривалість комутаційних інтерва-лів на періоді біля 10%. Для трансформаторів ПРК стрижневої конструкції знайдений та верифікований вираз, який пов'язує величину xs* з геометричними розмірами, питомими втратами матеріалу стрижня, перегріву, потужності навантаження та частоти, який дозволяє визначати необхідну величину ширину вікна стрижня. Визначена величина питомої ємності снаберних конденсаторів (на 1 А струму IGBТ, що комутується) для забезпечення приблизно двократного зменшення енергії снаберного вимикання IGBT відносно безснаберної комутації: від 0,5 нФ/А до 3 нФ/А для приладів різних класів та технологій. Для розширення струмового діапазону існування режиму ZVS у ланці ІН аж до холостого ходу, пропонується модернізація АРК. Отримані вирази для параметрів резонансних та інших неактивних комутаційних інтервалів в функції параметрів ПРК. Фізичне моделювання ПРК з асиметричною топологією ланки ІС на експериментальному прототипі номінальною потужністю 500 Вт для фотовольтаїки (з використанням MOSFET, частота 50 кГц, напруга ланки ІН 480 В, ланки ІС 20-40 В, незалежне керування, показало високу ефективність: виміряний ККД склав 97% для вихідної напруги 40 В та потужності навантаження 500 Вт. Розглянута доцільність використання ПРК як складової частини батарейних систем накопичення енергії для підсилюючого пункту системи тягового електроживлення залізниці постійного струму (напруга контактної мережі 2-4 кВ). Для ланки ІС з 4-квадрантним ключем симетричної топології, номінальний вихідний струм ПРК 200 А, ключі ІС класу 6,5 кВ, напруга ланки ІН 600 В, ключі цієї ланки класу 1200 В, частота 1000 Гц, для ключів ланки ІН комутаційні втрати біля 7% від статичних. Оцінка маси трансформатора – біля 1,3 т, акумуляторної батареї – від 7,5 до 22,5 т, що дозволяє розташувати їх на борту потяга.

Thesis for a Doctor of Science Degree in specialty 05.09.12 "Semiconductor Power Converters" – National Technical University "Kharkiv Polytechnic Institute", Kharkiv, 2020. The dissertation is devoted to the solution of the actual scientific and applied problem, which consists in the development of the theory and principles of construction of non-reversible bi-directional DC converters with transformer galvanic isolation, which are a type of two - stage DC/DC converters. In work carried out development and research of the such converters based on a relatively new and little researched concept - the concept of separated commutation. Converters with separated commutation (CSC) are built on the basis of inhomogeneous inverter-rectifier units: the topology of the one stage is based on voltage-source-inverter (VSI, or voltage-fed, VF) topology, and the topology of the other stage is based on current-source-inverter (CSI, or current-fed, CF) topology; the stages are connected by a transformer. A special algorithm for synchronous control of the both stages switches - algorithm of separated commutation (ASC) - provides favorable conditions for switching: for the VF stage switches the turning-on is natural (zero voltage switching, ZVS) and the turning-off is forced with the help of capacitive snubbers; for the switches of CF stage the turning-off is natural (zero current switching, ZCS) and the turning-on is forced with the help of inductive snubber (its role can be played by the transformer's leakage inductance). Limiting switching losses allows to increase the conversion frequency. The non-reversibility of the converter with the CF stage while maintaining the property of bi-directionality is ensured by the presence in the CF stage the four-quadrant switch (switches). Is given the quantitative substantiation of the advantage of using in the stage with a larger value of the DC voltage the CF topology with the ZCS switching off mode, and the VF topology with the ZVS switching on mode for another stage switches. the concept of "critical" conversion frequency in CSC with IGBT was introduced. It is such a conversion frequency above which the sum of static and turn-off IGBT's losses in the VF stage will be higher than the sum of static losses in IGBT and its serial diode switch diode in the CF stage at the same current and voltage values switching. At a frequency higher than the "critical", the use in a higher-voltage stage the CF topology gives advantages in the efficiency. Data are presented for the values of "critical" frequencies for IGBT of leading manufacturers of different voltage classes and technologies, according to which for voltage classes of devices above 1700 - 2500 V, the use the CF topology for high-voltage stageis attractive. Several modifications of CSC schemes are presented. For CSC with a bridge circuit with 4-quadrant switches based on MOSFET in the CF stage, the advantages and disadvantages of synchronous and independent control of the composite switches are identified. For CSC with IGBTs in CF stage, the use of a number of schemes with 4-quadrant switches was analyzed, with along with the bridge scheme with 4-quadrant switches, A comparative analysis using the criterias of the sum the voltage on the turn-on switches and switches' cost showed the advantage of a circuit with a series-connected to transform's winding 4-quadrant switch and bridge circuit on IGBTs with reverse diodes (6 IGBT instead of 8). For such a CSC for the mode of reverse energy transfer (from CF to VF) the presence of a resonant interval of recharging of snubber capacitors was discovered. To minimize the switches' current overloading advisable introduce to the transistors of emitter group in the CF stage the zero current sensors. A CSC with an asymmetric topology of the CF stage is proposed and investigated, in which the current of the secondary winding flows not through 4, but through 3 switches, which is an advantage. For the mode of direct energy transfer (from VF stage to CF stage), a new type of commutation was detected. When the 4-quadrant switch is switched on, it is forced switch on at zero voltage (FZVS), and despite the forced turning-on and abrupt increase of the its current, the switching losses are absent. The role of the transformer leakage inductance (LІ) as turning-on snubber of CF switches are analyzed. It is proposed to limit its value to a level that provides the relative total duration of switching intervals for a period of about 10%, which is equivalent to the relative value of the short-circuit voltage xs* of the transformer within 16%. For CSC transformers of rod design, a expression for xs* was found. It expression connects this val-ue with geometric dimensions, parameters of the core magnetic material (specific losses) for a given overheating, load power and frequency, which allows to determine the required the width of the core window. Based on experimental data and literature data, the value of the specific capacitance of snubber capacitors (per 1 A of IGBT switching current) was determined to provide approximately twofold reduction of the IGBT's turning-off energy with snubber relative to turning-off energy without snubber: from 0.5 nF/A to 3 nF/A for devices of different classes and technologies; the data can be used for appropriate estimates in the design of converters. In the cases of CSCs with both symmetric and asymmetric topology of the CF stages, in order to expand the current's range of the ZVS mode in VF stage up to idling, the modernization of ASC is proposed: when the transistors in VF stage are forcibly turned off, those transistors of the two-quadrant switches of the CF stage are switched on at the same time, for which at this moment the collector voltage is direct. In created short circuit con-tour the resonant recharging of snubber capacitors at any load current is carried out; at the end of recharging the transistors of the CF stage turn off naturally, in ZCS mode. Expressions for parameters of resonant and other inactive switching intervals as a function of CSC parameters are presented and confirmed by simulation modeling. Physical simulation of CSC with asymmetric topology of the CF stage on an experimental prototype with a nominal power of 500 W for photovoltaics (using MOSFET, frequency 50 kHz, voltage of VF stage 480 V and CF stage 20-40 V, independent control, showed high efficiency: measured efficiency was 97% for an output voltage of 40 V and a load power of 500 W. The expediency of using the proposed principles of construction of PRC as a component of battery energy storage systems for the amplifying point of the traction power supply system of the DC railway (catenary voltage 2 - 4 kV) was considered. A symmetrical topology with a 4-quadrant key is selected for the CF lstage, the nominal output current of the converter is 200 A, the CF switches have the class of 6.5 kV, frequency is 1000 Hz, the voltage of the VF stage is 600 V, the switches of this stage have class 1200 V, the switching losses for the switches of this stage are about 7% of static. Estimation of the mass of the transformer - about 1.3 tons, the battery - from 7.15 to 21.5 tons, which allows you to place them on board the train.
Non-reversible two-stage DC/DC converters with separated commutation
Keywords: автореферат дисертації; нереверсивні оборотні дволанкові перетворювачі постійної напруги; інвертор напруги; інвертор струму; природна комутація; снабери; розділена комутація; чотирьохквадрантні ключі; non-reversible bi-directional two-stage DC/DC converters; voltage-source-inverter; current-source-inverter; zero voltage switching; zero current switching; snubbers; separated commutation; IGBT; four-quadrant switches; 621.314.1